Bill - Todd, Roberto H. (My University, 1900)
In the House of Delegates of Porto Rico; December 6, 1900; Mr. Todd introduced the following Bill. Declaring the officer of Delegate to be incompatible with other offices.
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.